2020
DOI: 10.1111/crj.13144
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of non‐small cell lung cancer combined with chronic obstructive pulmonary disease: A systematic review and meta‐analysis

Abstract: Objective To investigate the effect of non‐small cell lung cancer (NSCLC) combined with Chronic Obstructive Pulmonary Disease (COPD) on prognosis, so as to provide help to clinical diagnosis and treatment. Methods PubMed, Web of Science and the Medline were used to retrieve studies reported from 1950 to 2019. If the study reported the prognosis of COPD with NSCLC, the study was included and the relevant information was extracted and the data analyzed. The standard mean deviation (SMD) of 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…And a 53% survival rate was reported by another study in critically ill cancer patients with respiratory failure 23 . Other respiratory disease such as chronic obstruction pulmonary diseases and emphysema can also cause poor prognosis of cancer patients admitted to ICU 24 .…”
Section: Discussionmentioning
confidence: 99%
“…And a 53% survival rate was reported by another study in critically ill cancer patients with respiratory failure 23 . Other respiratory disease such as chronic obstruction pulmonary diseases and emphysema can also cause poor prognosis of cancer patients admitted to ICU 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is a significant risk factor for the development of COPD, and COPD is a significant cause of death in lung cancer patients (70). Previous meta-analyses of the prognosis of non-small cell lung cancer with COPD have shown that COPD is an important factor in the development and progression of lung cancer and that COPD in combination with non-small cell lung cancer patients is linked to a poor prognosis, shorter survival, and higher mortality (71). Consistent with this, our study also found that COPD patients with combined malignancy had a higher mortality rate than COPD patients without combined malignancy.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Recently, Wu et al conducted a meta-analysis with 12 case-control studies and showed that patients with NSCLC concomitant COPD was associated with poorer OS than the absence of COPD. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 10 Wu et al investigated the effect of NSCLC concomitant with COPD on prognosis and indicated that COPD has a deleterious effect on survival. 11 Mostly of those studies were focused on NSCLC, and studies investigating the prognostic significance of COPD for SCLC patients are limited. In addition, previous studies focused on the association of lung cancer and COPD were mainly in Caucasian populations, relevant data in Asian populations was scanty.…”
Section: Introductionmentioning
confidence: 99%